2001
DOI: 10.1089/10430340152528101
|View full text |Cite
|
Sign up to set email alerts
|

How to Optimize In Vivo Gene Transfer to Cardiac Myocytes: Mechanical or Pharmacological Procedures?

Abstract: An efficient gene delivery system is a prerequisite for myocardial gene therapy. Among the various procedures studied so far, catheter-based percutaneous gene delivery to the myocardium through the coronary vessels seems the most relevant to routine clinical practice; however, the optimal conditions remain to be determined. We selectively infused adenoviral vectors encoding luciferase (1 x 10(9) PFU) or beta-galactosidase (1 x 10(10) PFU) into coronary arteries of adult rabbits in various experimental conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
66
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 22 publications
1
66
0
2
Order By: Relevance
“…A cardiac arrest of 2 min (1.5 min transfection time) allowed to transfect 18% of CMs in rats, whereas an extended viral incubation time up to 4.5 min extended the positive CMs to 43%, suggesting that transfection efficiency correlates directly with viral incubation time. Similar to our results, Logeart et al 13 showed that a brief interruption of coronary flow is required to obtain significant gene transduction in vivo and the efficiency tended to increase with the time period of coronary artery occlusion. In the hamster model, Ikeda et al 3 recently demonstrated that the short incubation time (10-20 s) in single-pass manner yielded only 4-5% of myocardial gene transduction compared to a much higher efficiency when the incubation time was extended to 5 min during hypothermia together with cross-clamping of the ascending aorta and main pulmonary artery.…”
Section: Optimization Of Gene Deliverysupporting
confidence: 92%
See 4 more Smart Citations
“…A cardiac arrest of 2 min (1.5 min transfection time) allowed to transfect 18% of CMs in rats, whereas an extended viral incubation time up to 4.5 min extended the positive CMs to 43%, suggesting that transfection efficiency correlates directly with viral incubation time. Similar to our results, Logeart et al 13 showed that a brief interruption of coronary flow is required to obtain significant gene transduction in vivo and the efficiency tended to increase with the time period of coronary artery occlusion. In the hamster model, Ikeda et al 3 recently demonstrated that the short incubation time (10-20 s) in single-pass manner yielded only 4-5% of myocardial gene transduction compared to a much higher efficiency when the incubation time was extended to 5 min during hypothermia together with cross-clamping of the ascending aorta and main pulmonary artery.…”
Section: Optimization Of Gene Deliverysupporting
confidence: 92%
“…[12][13][14] Among the parameters tested, it was not surprising that prolongation of viral transfection time within the heart is important to elevate the efficiency of myocardial transfection. Having solved this problem by our cardiac arrest protocol, we could optimize the transfection efficiency.…”
Section: Optimization Of Gene Deliverymentioning
confidence: 99%
See 3 more Smart Citations